Design and operation of a pilot-scale catalytic biomass pyrolysis unit. Issue 9 (14th August 2015) - Dayton, David C.; Carpenter, John R.; Kataria, Atish; Peters, Jonathan E.; Barbee, David; Mante, Ofei D.; Gupta, Raghubir
<x xml:space="preserve">Abstract</x> Pilot-scale catalytic biomass pyrolysis unit for producing low oxygen content, thermally stable bio-crude for upgrading into advanced biofuels.